The prevalence of neural antibodies in temporal lobe epilepsy and the clinical characteristics of seropositive patients. (December 2018) - Elisak, Martin; Krysl, David; Hanzalova, Jitka; Volna, Kamila; Bien, Christian G.; Leypoldt, Frank; Marusic, Petr
Highlights: 5% prevalence of neural surface and GAD antibodies in temporal lobe epilepsy patients. All positive patients had unknown epilepsy aetiology. Positivity associated with higher age at epilepsy onset and autoimmune comorbidity. Immunoresponse observed in half of positive patients. Abstract: Purpose: Epileptic seizures are a common manifestation of autoimmune encephalitis, but the role of neural antibodies in long-term epilepsy remains unclear. The aim of this study was to assess the prevalence of neural-surface antibodies (NSAbs) and antibodies against glutamic acid decarboxylase (GAD) in patients with chronic temporal lobe epilepsy (TLE). Method: Patients with an electro-clinical diagnosis of TLE and a disease duration longer than one year were included. NSAbs (LGI1, CASPR2, AMPAR1/2, NMDAR, GABAB R) and antibodies against GAD were detected. Only patients with significant antibody levels in serum, and/or positivity in CSF (according to antibody subtype), were enrolled in the seropositive group. Cohorts of seropositive and seronegative patients were compared regarding clinical and imaging data. Results: Significant serum levels of antibodies were detected in eight out of 163 (5%) TLE patients (CASPR2 n = 2, GAD n = 3, LGI1 n = 2, and GABAB R n = 1). In four of them, antibodies were detected in the CSF as well (CASPR2 in one, GAD in three). Five seropositive patients had uni- or bilateral temporal lobe lesions on MRI and three patients were non-lesional. All seropositive patients had TLE of unknown cause. Seropositive patients had higher age at epilepsy onset and autoimmune comorbidity, but did not differ in other clinical, EEG or neuroimaging characteristics. Response to immunotherapy (seizure reduction >50%) was observed in three of the six patients treated. Conclusions: Besides older age at epilepsy onset and autoimmune comorbidity, seropositive patients cannot be distinguished from seronegative patients on the basis of clinical, EEG or neuroimaging data.